UNDERSTANDING SPORT EVENT VISITORS’ MOTIVATION AND SATISFACTION OF SMALL-SCALE SPORT EVENT - ANISAH ABDUL WAFI; Lim Khong Chiu; Kalsom Kayat, (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
The purpose of this paper is to have further understanding on the visitors’ motivation and satisfaction in attending the small-scale sport event particularly in northern peninsular of Malaysia. Understanding of the factor that motivates visitors’ to attend the sport event and what influence their satisfaction becomes important for the event organizer and the marketing purposes. Through this understanding, the sport event can be organized according to the needs and demands of the visitors’. As the main purpose of the small-scale event is to give the benefits to the local community, understanding these factors becomes important to ensure the success. Hence, this study applied the push and pulls model in order to examine the visitors’ motivation and satisfaction that influence the visitors’ to attend this small-scale sport event. Finding showed that visitors’ motivate to attend this event to earn the knowledge and to escape from the routine life. Moreover, the visitors’ significantly satisfied with facilities and convenience. This finding becomes valuable information for event organizer for their strategic planning and marketing purposes.